Hydrological Response to Rewetting of Drained Peatlands—A Case Study of Three Raised Bogs in Norway - Marta Stachowicz; Anders Lyngstad; Paweł Osuch; Mateusz Grygoruk (Land)
The proper functioning of peatlands depends on maintaining an adequate groundwater table, which is essential for ecosystem services beyond water retention. Most degraded peatlands have been drained for agriculture or forestry primarily through ditch construction. Rewetting through ditch blocking is the most common initial step in peatland restoration. This study analyzed the hydrological response to ditch blocking in three drained raised bogs in Norway (Aurstadmåsan, Midtfjellmåsan and Kaldvassmyra) using a Before–After–Control–Impact (BACI) design. Following rewetting, all sites demonstrated an average increase in groundwater levels of 6 cm across all piezometers affected by ditch blocking. The spatial influence of ditch blocking extended 12.7–24.8 m from the ditch with an average of 17.2 m. Additionally, rewetting increased the duration of favorable groundwater levels for peatland functioning by 27.7%. These findings highlight the effectiveness of ditch blocking in restoring hydrological conditions, although its impact is spatially limited. Future assessments should also address vegetation recovery and greenhouse gas emission reductions to ensure comprehensive restoration success.